Tocqueville and Democracy in the Internet Age - Jon Delogu, C. (Open Humanities Press, 2014)
Tocqueville and Democracy in the Internet Age is an introduction to Alexis de Tocqueville (1805-1859) and his monumental two-volume study Democracy in America (1835, 1840) that pays particular attention to the critical conversation around Tocqueville and contemporary democracy. It attempts to help us think better about democracy, and also perhaps to live better, in the Internet Age.